Indian manufacturing sector in post-reform period : an assessment of the role of macroeconomic and firm-specific factors in determining financial performance /: an assessment of the role of macroeconomic and firm-specific factors in determining financial performance. (2022) - Maji, Sumit Kumar; Laha, Arindam, 1979-; Sur, Debasish
No abstract available